Women Entrepreneurship and Sustainable Economic Development: Evidence from Nigeria - Sajuyigbe, Dr. Ademola Samuel; Fadeyibi, Isaac Olugbenga (Journal of Entrepreneurship, Business and Economics, 2017)
The emerging field of entrepreneurship in 20th century has made women entrepreneurs to be creative and innovative. However, in Africa especially Nigeria, women have historically been disadvantaged in accessing not only material resources, but also have been deprived of resources like finance, market information and modern technology. This study examined the influence of women entrepreneurs on sustainable economic development in Nigeria. Other specific objectives were to  assess the perceived contributions of women entrepreneurs to economic sustainability in Nigeria; ascertain the ways in which women entrepreneurs have been empowered; determine the factors motivating women into entrepreneurship  and to identify the major challenges facing women towards entrepreneurship development in Nigeria. This research work was carried out among the three thousand one hundred and fifty (3,150) women entrepreneurs registered with ministry of commerce and industry in the South-Western geo-political zones of Nigeria. A total of six hundred and eighty (680) participants were selected as sample size for the study. The data collection instruments for the study were structured questionnaire and personal interview. Data analysis was performed with the aid of simple percentage, mean, chi-square and linear Regression. Results revealed that involvement of women in entrepreneurship (β = 0.310, t = 17.175, P<.001) have positive and significant influence on sustainable economic development. Results also indicated that majority of women have been empowered by voting in elections, have access to education, and they have benefited from empowerment training. Furthermore, result indicated that involvement of women in entrepreneurial activities accounted for 30.3% of the variation which was explained by the model while extraneous variables accounted for about 69.7%.  Results so revealed that lack of access to finance, work/home conflict and lack of moral support from family members are major challenges facing women entrepreneurs in Nigeria. Study concluded that involvement of women in entrepreneurship is a catalyst to the sustainable economic development. The study recommended the establishment of Women Entrepreneurship Development Centre (WEDC) by the federal/state government in collaboration with private sector to provide financial assistance, business advice, mentorship and other practicable support in order to empower the Nigerian women towards realization of the self-employment aspirations. Research paper Keywords: Women Entrepreneurs, Entrepreneurship, Sustainable Economic Development, Challenges Reference to this paper should be made as follows: Sajuyigbe, A. S., & Fadeyibi, I. O. (2017). Women Entrepreneurship and Sustainable Economic Development: Evidence from South Western Nigeria, Journal of Entrepreneurship, Business and Economics , 5(2), 19–46.